2016
DOI: 10.1136/bmjqs-2016-005567
|View full text |Cite
|
Sign up to set email alerts
|

Nursing skill mix in European hospitals: cross-sectional study of the association with mortality, patient ratings, and quality of care

Abstract: ObjectivesTo determine the association of hospital nursing skill mix with patient mortality, patient ratings of their care and indicators of quality of care.DesignCross-sectional patient discharge data, hospital characteristics and nurse and patient survey data were merged and analysed using generalised estimating equations (GEE) and logistic regression models.SettingAdult acute care hospitals in Belgium, England, Finland, Ireland, Spain and Switzerland.ParticipantsSurvey data were collected from 13 077 nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
481
5
44

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(551 citation statements)
references
References 41 publications
21
481
5
44
Order By: Relevance
“…These results are consistent with the findings of other studies (1,8,(18)(19)22) , which indicate that better nurse staffing and the consequent increase in nursing hours for the patient have significant association (p<0.01) with lower rates of pressure ulcers, pneumonia, falls and sepsis, as well as with a reduction in medication errors and mortality. Thus, it is understood that the increase in the number of patients assigned to nurses is associated with negative quality and safety outcomes for hospitalized patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the findings of other studies (1,8,(18)(19)22) , which indicate that better nurse staffing and the consequent increase in nursing hours for the patient have significant association (p<0.01) with lower rates of pressure ulcers, pneumonia, falls and sepsis, as well as with a reduction in medication errors and mortality. Thus, it is understood that the increase in the number of patients assigned to nurses is associated with negative quality and safety outcomes for hospitalized patients.…”
Section: Discussionsupporting
confidence: 92%
“…In European countries, the data found showed a variation of registered nurses in inpatient units ranging from 54% in Spain to 82% in Germany (26) . Recent research in European countries concluded that bedside care workforce with a higher proportion of professional nurses was associated with better patient outcomes and better working and safety conditions at the hospitals (22) . However, despite the growing evidence on the causal relationship between nurse staffing and better outcomes for the patients, the findings are still inconsistent when regarding the financial aspects involved in the adoption of policies for adequate nurse staffing in practice scenarios, both in international and Brazilian contexts.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, nursing researchers continue to reiterate that increased staffing by qualified nurses reduces patient mortality and morbidity. 6 Both in the US and in NHS STPs, there is strong advocacy of hospital mergers. Evidence of the cost effectiveness of this policy is sparse with US studies showing less concentrated markets have better quality care and lower prices.…”
Section: The Public Servants' Reactionmentioning
confidence: 99%
“…International studies, such as the one carried out in 243 hospitals in 6 European countries (4) and another carried out in 60 hospitals in South Korea (5) , show that there is a direct correlation between adequate care staff in quantity and quality with the assistance results involving directly the patient's safety and the quality of the services offered.…”
Section: Introductionmentioning
confidence: 99%